COMPARISON ANALYSIS OF SPELLING MISTAKES ON DETIKCOM AND KOMPAS.COM - Siti Nurhaliza Safitri; Wahyunengsih (Journal of Innovation Research and Knowledge, 2023)
The purposes of this study are: 1) To find out whether there are spelling mistakes in Detikcom and Kompas.com online newspapers. 2) To find out what types of spelling mistakes are often found in Detikcom and Kompas.com online newspapers. 3) To compare which online newspaper has fewer spelling mistakes. This research uses the descriptive qualitative method with document analysis instruments and simak-catat technique. It can be concluded that: 1) There were 60 spelling mistakes in 40 news headlines from Detikcom and 37 spelling mistakes in 40 news headlines from Kompas.com. 2) Italicization mistakes are often found in Detikcom with as many as 45 mistakes, while word writing mistakes are often found in Kompas.com with as many as 17 mistakes. 3) Kompas.com has fewer spelling mistakes than Detikcom in the March-April 2023 edition.